Community Empowerment to Prevent Stunting Through Integrated Health Promotion in Cilayung Village, Jatinangor Sub-District - Mamat Lukman; Ahmad Yamin; Raini Diah Susanti (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2023)
ABSTRACT Stunting is a growth disorder or a short (dwarf) child's height compared to his age standard. Of the problems that occurred in Cilayung Village, out of 517 toddlers, 12 experienced stunting and delays in thinking processes. This report provides an overview of community empowerment to increase community knowledge and skills in stunting prevention through integrated health promotion programs. This community empowerment program is carried out using a hybrid method. Preparatory activities are carried out offline and online, while extension and training implementation activities are carried out directly or offline. The results of the community empowerment program show that it can increase community knowledge and participation in efforts to prevent stunting in Cilayung Village, Jatinangor District. Much of the increase in public understanding and awareness is related to the importance of exclusive breastfeeding for infants, food processing for toddlers aged 2-5 years, maternal reproductive health and nutritious diets for children, and early stimulation for children in preventing stunting. The integrated stunting prevention health promotion program is expected to become one of the additional programs that aim to prevent stunting in Indonesia by developing capabilities and independence through community empowerment. Keywords: Community Empowerment, Health Promotion, Integrated Programs, Prevention, Stunting